Wo-MENA paradox: glass ceiling or sticky floor? - Kerras, Hayet; Bautista, Susana; de-Miguel Gómez, María Dolores (Journal of North African Studies, 2023)
Despite the progress made by the countries of the Middle East and North Africa (MENA) region in terms of gender equality and social and, above all, educational emancipation, today there are still disparities in terms of the participation of women in the labour market. This paper proposes a descriptive and qualitative analysis of the situation of women in two MENA countries, which are Algeria and Morocco, and of the socioeconomic factors that hinder their autonomy in the field of work. As a result, the role of the family and the social environment on women is emphasised so that they could be active members of society and consequently become an additional labour force trained for the growth of the region, is emphasised, but it is condemned for the achievement of this triple challenge: education, professional integration, and economic empowerment.